Target balances and financial crises - Jan Pieter Krahnen (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2019)
Recently, Fuest and Sinn (2018) have demanded a change of rules for the Eurozone's Target 2 payment system, claiming it would violate the Statutes of the European System of Central Banks and of the European Central Bank. The authors present a stylized model based on a set of macro-economic assumptions, and show that Target 2 may lead to loss sharing among national central banks (NCBs), thus violating the no risk-sharing requirement laid out by the Eurosystem Statutes. In this note, I present an augmented model that incorporates essential features of the micro- and macroprudential regulatory and supervisory regime that today is hard-wired into Europe's banking system. The model shows that the original no-risk-sharing principle is not necessarily violated during a financial crisis of a member state. Moreover, it shows that under a banking union regime, financial crisis asset value losses at or below the 99.9th percentile are borne by private investors, not by taxpayers, and particularly not by central banks. Therefore, policy conclusions from the micro-founded model differ significantly from those suggested by Fuest and Sinn (2018).
urn:nbn:de:hebis:30:3-487990
Keywords: 330; Target 2; payment system; central banks; Eurosystem